HUBUNGAN TERPAANTVLOG TUTORIAL MAKE.UP DI YOUTUBE TERHADAP MINAT BELAJAR MAKE UP REMAJA KOTA DENPASAR - Nendissa Hermawan, I Gusti Ayu Rara; Alit Suryawati, I Gusti Agung; Pradipta, Ade Devia (E-Jurnal Medium, 2019)
ABSTRACT YouTube as a medium for channeling people’s creativity, It can also be conducted through the internet one of them is through make up tutorial vlog on YouTube in which the contents usually contain complete information steps to apply makeup. Purpose of this research is to study the correlation of exposure towards makeup tutorial vlog on YouTube towards the interest to learn makeup on Denpasar teenagers. This research uses quantitative method. The sample collecting method is non-probability sampling. Data is obtained through questionnaire. The result of this research showed that the correlation of exposure towards makeup tutorial vlog on YouTube towards the interest to learn makeup on Denpasar teenagers indicated as positive and in the same direction, meaning that the more exposed Denpasar teenagers to makeup tutorial vlog on YouTube, the higher the interest of Denpasar teenagers to learn makeup.    Keywords: Correlation, Interest to Learn, Makeup Tutorial Vlog Exposure, YouTube